2022
DOI: 10.3389/fpls.2022.999058
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress proteins in plants: An overview

Abstract: Salinity stress is considered the most devastating abiotic stress for crop productivity. Accumulating different types of soluble proteins has evolved as a vital strategy that plays a central regulatory role in the growth and development of plants subjected to salt stress. In the last two decades, efforts have been undertaken to critically examine the genome structure and functions of the transcriptome in plants subjected to salinity stress. Although genomics and transcriptomics studies indicate physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 322 publications
0
11
0
Order By: Relevance
“…It has been shown that salt concentrations which are harmful to one plant species may not be stressful for another. Previous investigations showed that changes in the proteins of PSII (LHCII, inner antenna of PSII, D1 and OEC) and PSI as well as the degree of the inhibition of photosynthetic performance depend on the salt sensitivity of the plant species [ 18 , 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that salt concentrations which are harmful to one plant species may not be stressful for another. Previous investigations showed that changes in the proteins of PSII (LHCII, inner antenna of PSII, D1 and OEC) and PSI as well as the degree of the inhibition of photosynthetic performance depend on the salt sensitivity of the plant species [ 18 , 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data revealed a stronger decrease in the amount of Chl a than Chl b in leaves ( Figure 1 ), which could be a result of the influence on pigment biosynthesis and degradation [ 51 ]. Previous observations have demonstrated that Chl a is more salt-sensitive than Chl b and the primary reason for the decrease in the Chl content after salt stress is the degradation of Chl a [ 28 ]. The other reason for the reduction in the Chl content could be the decreased biosynthesis of the LHCII chlorophylls [ 46 , 72 ], which corresponds with an increase in the Chl a/b ratio and a decrease in the degree of thylakoid stacking [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess ROS can cause oxidative damage, and thus a strong inhibition of photosynthetic activity [ 5 ]. It has also been shown that salinity modified the contents of several thylakoid membrane polypeptides, including the D1 protein and some polypeptides related to light utilization and oxygen-evolving activity [ 12 , 13 , 14 ]. The observed alterations in the thylakoid membranes and the photosynthetic functions are connected with a decrease in the density of the photosynthetic structures, the relative size of the plastoquinone (PQ) pool, the electron transport to the photosystem I (PSI) end electron acceptors and the probability of their reduction, as well as to an increase in the thermal energy dissipation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation of cucumber on the NUGE medium resulted in a decrease in the soluble protein content ( Figure 2 D). Plant tissues respond to salt stress by degrading proteins or producing abundant salt stress-related proteins [ 52 ]. Soluble proteins accumulated in plants under salt stress play a key role in osmoregulation but also protect cell membranes, and enzymes from Na + toxicity.…”
Section: Discussionmentioning
confidence: 99%